Exploring profitability changes in hospitality industry: An econometric and statistical perspective - Pericleous, Katerina; Kosmas, Petros C.; Theocharous, Antonis L.; Ioakimoglou, Elias; Andreev, Christos (My University, 2023)
The aim is to analyse profitability indicators within the hospitality industry comprehensively. This will be achieved by utilising a well-established empirical framework by studying the capital profitability of the Republic of Cyprus. Furthermore, the variations in the rate of return on fixed capital and identifies the key variables influencing profitability will be examined. The data analysed is from 2005 to 2020. Employing rigorous statistical analysis and econometric modelling, it untangles the intricate relationship between profitability indicators and the multifaceted factors shaping the financial performance of the hospitality sector. The method also endeavours to discern distinct capital valorisation and accumulation phases, providing valuable insights into the fundamental dynamics at play. The findings reveal significant implications for industry stakeholders, policymakers, and researchers, as they offer actionable recommendations and a comprehensive understanding of the profitability dynamics in the Republic of Cyprus hospitality industry. Additionally, it sets a stepping stone for future endeavours and contributes to advancing econometrics and statistics in the field.
Keywords: Econometric modelling; Multivariate analysis; Return predictability